The larval development of Pinnixa gracilipes Coelho (Decapoda, Pinnotheridae) reared in the laboratory - Lima,Jô de F. (2006)
Pinnixa gracilipes Coelho, 1997 is a small pinnotherid crab living in association with ghost shrimp Lepidophthalmus siriboia Felder & Rodrigues, 1993 in the northeastern region of Pará State, Brazil. Larvae of P. gracilipes were reared in the laboratory from hatching to the megalopa stage. The complete zoeal period averaged 24 days. Mean duration for each larval stage was 5, 4, 4, 5 and 6 days, respectively. In the present study, five zoeal and megalopal stages are described and illustrated in detail. Morphological comparisons with previous reported works on Pinnotheridae larvae are briefly discussed.